Effect of dietary inclusion of fresh or dry duckweed (Lemna pepusulla) on the performance of broiler - KHATUN, M J; CHOWDHURY, S A; SALAUDDIN, M; KHAN, M K I (The Indian Journal of Animal Sciences, 2014)
The experiment was conducted to determine the effect offeeding diet containing fresh or dry duckweed (DW) on the performance of broilers. Day- old broilers chicks were randomly allocated into 3 treatments, each having 3 groups of 11 birds. The 3 treatments were 3 iso-caloric and iso-nitrogenous diets; a control diet (diet C), partially replaced either with 6% of fresh DW (diet A)or with 7% of dry DW (diet B). There was no difference among the treatments on respect of average feed consumption, weight gain, feed conversion ratio and carcass traits. Inclusion of DW (ether fresh or dry condition) signititantly (P<0.05) reduced the feed cost of individual broiler. Thus the result of present study suggests that small amount (6% dry matter basis) fresh or dry DW can be incorporated for profitable broiler production.